Beginning C from beginner to pro - Gonzalez-Morris, German; Horton, Ivor (Apress, 2024)
Learn how to program using C, beginning from first principles and progressing through step-by-step examples. This seventh edition is fully updated to reflect new features of C23, and addresses deprecated functions and features that are no longer supported. You'll discover that C is a foundation language that every programmer ought to know. Beginning C is written by renowned author Ivor Horton and expert programmer German Gonzalez-Morris. This book increases your programming expertise by guiding you through the development of fully working C applications that use what you've learned in a practical context. Examples of how to use deprecated functions are also provided, along with new examples for replacing them when a simple solution is possible. By the end of the book you'll be confident in your skills with all facets of the widely-used and powerful C language and be able to strike out on your own by trying the exercises included at the end of each chapter. All you need are this book and any of the widely available C compilers, and you'll soon be writing real C programs.
Includes index
Keywords: C (Computer program language); C (Langage de programmation)